Penerapan Asas Proposionalitas dalam Kontrak Layanan Kesehatan antara Rumah Sakit dan Badan Penyelenggara Jaminan Sosial (Bpjs) - Solikah Sriningsih (Faculty of Law- Hang Tuah University, 2021)
This study is to determine the relationship between the health service cooperation contract between the hospital and the Social Security Administration (BPJS). and to see that the principles of proportionality have been applied in the cooperation contract between the hospital and the Social Security Administering Body (BPJS). Types of health service cooperation contracts between hospitals and the Social Security Administering Bodies (BPJS) are as follows: a. Formed from two parties, namely the Social Security Administering Body (health insurance agency) and the hospital (health service provider). And b. The Social Security Administering Body has the responsibility of collecting and assisting health insurance program participants who then come from the hospital as the health provider for BPJS program participants.The application of the principle of proportionality in the cooperation contract between the hospital and the Social Security Administration (BPJS) in the implementation has been applied to all stages of the contract including: contract, contract implementation, and post-contract. The principle of proportionality animates in all stages of the contract where in principle there has been a transfer of rights and obligations according to the burdens and responsibilities of each party.